Surface doping of ZnO nanowires with Bi: Density-functional supercell calculations of defect energetics - Aras, Mehmet; Kilic, Cetin (Amer Physical Soc, 2019)
Defect calculations using the density and hybrid functionals in combination with the supercell approach are employed to characterize the electrical properties of a number of ZnO nanowires of various thicknesses doped with Bi atoms occupying surface sites. The variation of the differences between the total energies of charged and neutral supercells with the supercell size is studied, which led the authors to devise an extrapolation procedure to obtain reliable defect energetics in the dilute defect limit. The calculated defect formation energies indicate that although the substitution of Bi into Zn or O sites can take place spontaneously under suitable thermodynamic conditions, the substitution into Zn sites is generally more likely. The defect (charge-state) transition energies are computed and parameterized as a function of the nanowire thickness. It is revealed that the substitution of Bi into O (Zn) sites on the surface of ZnO nanowires yields deep acceptor (shallow donor) levels (except for extremely thin nanowires). It is therefore concluded that the incorporation of Bi into the surface of ZnO nanowires results in n-type doping.
Keywords: Total-Energy; Oxide; Co; Nanostructures; Bismuth